846 Neospora caninum – an immunotherapeutic protozoan against solid cancers. (9th November 2020) - Lantier, Louis; Poupee-Beauge, Agathe; Lantier, Louis; Ducournau, Céline; Tommaso, Anne Di; Germon, Stéphanie; Moiré, Nathalie; Lee, Gordon; Touze, Antoine; Dimier-Poisson, Isabelle
Abstract : Background: Immunotherapy induces, provides, and/or reactivates anti-tumor immune responses. Some microorganisms also can initiate response that lyzes infected tumor and/or stimulates systemic immunity. Attenuated viruses or bacteria are well studied as oncotherapeutics, but not protozoa except Toxoplasma gondii. 1 We assessed the effect on tumors of other protozoa that were naturally non-pathogenic to humans. Thus, we discovered the ability to use Neospora caninum (Nc) in a manner and form that demonstrated a synergistic array of pertinent immunotherapeutic characteristics against solid cancers. Our first Article on Neospora as Onco-immunotherapeutic is currently under revision after review by the JITC. We report on the most recent data notably from Nc engineered to secrete human IL-15 within the tumor. Methods: In vitro, the immunostimulatory properties of Nc strains wildtype and engineered to secrete human IL-15 were studied. In vivo experiments of treatment with of Nc tachyzoites 2 administered locally (intra and peri tumoral) or remotely (subcutaneous) in a murine thymoma EG7 tumor and in human Merkel cell carcinoma (MCC). Results: We demonstrated that the treatment of thymoma EG7 by Nc strongly inhibited tumor development. Analysis of immune responses and interactions between Nc and tumor cells showed that Nc had the ability to lyze infected cancer cells, reactivated immune competence within the Tumor Microenvironment (TME), and activated the systemic immune system by promoting the recruitment of immune cells to the site of tumor. We also established in a NOD/SCID mouse model that Nc was able to induce a strong regression of human MCC. Recently, to further enhance oncotherapeutic effect, we engineered an Nc strain to secrete human IL-15 (cross reactive with mouse cells), associated with alpha subunit of IL-15 receptor, increasing its stability. 3 This strain induced proliferation of human PBMCs and their secretion of IFN-γ. In the EG7 model, human IL-15 secreting Nc showed greater protection against tumor development, confirming enhancement of immunotherapy by engineering Nc to deliver/secrete IL-15. Conclusions: These results highlight Neospora caninum as a potentially extremely efficient, and non-toxic anti-cancer agent, capable of being engineered to express at its surface or to secrete bio-drugs, like human IL-15 cytokine. Our work has identified the broad clinical possibilities of using N. caninum as an oncolytic protozoan in human medicine capable of vectoring molecular therapy, overcoming TME defenses. References: Fox BA, Butler KL, Guevara RB, Bzik DJ. Cancer therapy in a microbial bottle: Uncorking the novel biology of the protozoan Toxoplasma gondii. PLoS Pathog 2017;13(9):e1006523. https://doi.org/10.1371/journal.ppat.1006523 Bjerkas I, Jenkins MC, Dubey JP. Identification and characterization of Neospora caninum tachyzoite antigens useful for diagnosis of neosporosis. Clin Diagn Lab Immunol 1994;1(2):214-221. Article for publication in the Journal of Immunotherapy of Cancer, under revision on September 20, 2020.